Effects of Rotifer Feeding Frequency on Growth and Survival Rate of Early Larval Stages of Mud Crab, Scylla olivacea - Chrisoetanto P. Pattirane; Bethsy J. Pattiasina; Frederik Dony Sangkia (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2021)
Crustacean larvae have the characteristics of living as carnivorous organisms. This has an impact on the length of gut evacuation time which affects the feeding pattern of the larvae. The feeding strategy of mud crab larvae is modulated by the length of gut evacuation time. Another factor that can be subject to modulation is the frequency of feeding. This research aimed to evaluate rotifer frequency feeding of early larvae stages of mud crab, Scylla olivacea. This research was conducted at the Mariculture Fisheries Center, Ambon with an indoor system. This research began with carrying out parental maintenance to produce larvae. Larvae are fed with rotifers with different frequencies. The treatments were the frequency of feeding rotifers, namely: Treatment 1 (F1) was the frequency of 1x a day (9:00 am); Treatment 2 (F2) was a frequency of 2x a day (9:00 am & 13:00 pm) and Treatment 3 (F3) was a frequency of 3x a day (9:00am, 13:00pm & 17:00pm). Each treatment was given 3 replications. Based on the results of this study, it showed that feeding with a frequency of three times a day (F3 treatment) was able to have a positive effect on the survival rate of zoea larvae which on the third day was 58% and the fourth day was 22% higher than the F1 and F2 treatments. The growth of larvae showed that F3 treatment was higher than F1 and F2 on the sixth day with an increase in the absolute value of growth of 0.12044 mm compared to F1 of 0.05531 mm and F2 of 0.03253 mm.Â Keywords: frequency of feeding, growth, larvae, survival rate, mud crab